The Analysis of Cassava Farming in Buton Central District: Income and Feasibility - Munirwan Zani; Lukman Yunus; Surni Surni (Department of Agribusiness Halu Oleo University Kendari Southeast Sulawesi, 2022)
This research investigates the profitability and viability of Cassava growth in the Central Buton Regency. This research was conducted in March - April 2020 in Central Buton Regency. Cassava growers from Central Buton Regency made up the study's population of 48 persons. The census technique is used to determine the sample size. Primary and secondary data are the two types and sources of research data. Direct interviews and literature studies are two methods for gathering data for research. Research variables include variable costs, fixed costs, total costs, price, production, revenue, and income. Utilizing income analysis and R/C ratio analysis, the data were analyzed. According to the data, cassava farming in Central Buton Regency generated IDR2.828.081 every season. With an R/C ratio value of six, Cassava growing in the Central Buton Regency is economically feasible